Evaluasi Usability Website Menggunakan System Usability Scale Pada Aplikasi SIPD e-BMD Pemerintah Kota Salatiga - Sulistyanti, Yeni Sri (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2025)
This study aims to measure the usability level of the Regional Government Electronic Information System for Regional Property (SIPD e-BMD) application using the System Usability Scale (SUS). The SIPD e-BMD application is part of the SIPD application, designed and developed by the Ministry of Home Affairs of the Republic of Indonesia which is mandatory for local governments to use, but there are not many studies evaluating its usefulness or usability. The Salatiga City Government has been using the SIPD e-BMD for more than two years but the output of the application is not yet fully usable especially for financial reports so it is necessary to conduct a usability evaluation. The data used in this study are primary data obtained through questionnaires, observations and interviews with application users to obtain information related to user perceptions. The collected questionnaire data were then analyzed to calculate the SUS score and assess the level of usability of the application. The results showed that the SIPD e-BMD application obtained a SUS score of 49.3. This scale indicates that the application is starting to be accepted by users. This application has several advantages including ease of use, an adequate system for archiving data, providing a complete report format and a system flow that complies with regulations. However, this application still has weaknesses, including that the calculations in the depreciation report are not yet accurate and it takes time to troubleshoot.